Analysis of the Use of Social Network in the 21st Century Active Learning for Undergraduate Students Based on the Subject of Rapid Application Development - Orawit Thinnukool (2018)
© 2018 World Scientific Publishing Company. The correlation between learning styles in a classroom and suitable tools to facilitate learning directly affect learning outcomes Characteristics of students nowadays have been changed by the modern world of technology. Generation Z students have a different concept of what is interesting, challenging and satisfying which in turn, affects learning outcomes. Thus, to achieve a better learning outcome, a suitable learning style and tool to support learning are needed. This paper aims to research and test learning outcomes of students who studied the subject of rapid application development, which was a computational application development course. Two groups of students used two different learning styles: the active learning style and traditional style. The results show a statistical analysis, which was used to compare the learning outcomes and student's satisfaction. The active learning style indicates that those students who used this had a higher level of effective learning than the students who studied traditionally. Regarding analysis, the learning outcomes and satisfaction of the two learning styles are discussed.